Amalgam Tattoo Mimicking Mucosal Melanoma: A Diagnostic Dilemma Revisited. (6th March 2013) - Lundin, K.; Schmidt, G.; Bonde, C.
Abstract : Mucosal melanoma of the oral cavity is a rare but highly aggressive neoplasm. However, the clinicians need to be aware of the other and more frequent etiologies of intraoral pigmentation, such as amalgam tattoos. As amalgam has been extensively used for dental restorations and can cause pigmentations in the oral mucosa, this is a differential diagnosis not to be forgotten. We describe the characteristics of these two phenomena and present a case vignette illustrating the differential diagnostic issues. Other causes of intraoral pigmentation are summarized.